2017
DOI: 10.1039/c7dt00881c
|View full text |Cite
|
Sign up to set email alerts
|

Molecular conductors from bis(ethylenedithio)tetrathiafulvalene with tris(oxalato)rhodate

Abstract: This article reports a family of new radical-cation salts of bis(ethylenedithio)tetrathiafulvalene (BEDT-TTF) with tris(oxalato)rhodate: three salts with the formula β''-(BEDT-TTF)[(cation)Rh(CO)]·solvent (solvent = fluorobenzene, chlorobenzene, or bromobenzene) and one with the formula pseudo-κ-(BEDT-TTF)[(NH)Rh(CO)]·benzonitrile. We report here the syntheses, crystal structures, electrical properties and Raman spectroscopy of these new molecular conductors. The bromobenzene salt shows a decrease in resistivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 45 publications
(16 reference statements)
1
18
0
Order By: Relevance
“…Figure 4. Electrical resistivity for Al-PhBr.The Al 3+ ion of tris(oxalato)aluminate is smaller than previous examples, where M = Fe[13,17], Ga[28], Rh[30], and Ru[29] (T c =~3.8,~3.0,~2.9,~2.8 K, respectively, for G = bromobenzene), and the T c is smaller for M = Al at~2.5 K. A comparison of the b axis length of these bromobenzene salts at room temperature showed that the M = Fe salt has the longest at 20.0546(15) Å and also the highest~3.8 K [13,17]; M = Rh has an intermediate b axis of 20.0458(4) Å and a T c of~2.9 K [30]; while M = Al has the shortest b axis of 19.9472(4) Å and the lowest T c at~2.5 K. A direct comparison with the M = Ga[28] and Ru[29] salts cannot be made owing to A = K x (H 3 O) 1-x rather than H 3 O for these salts. Salts with M = Cr[23] and Mn[17] have been reported with T c s of 1.5 K and 2.0 K, respectively, but crystal structures are not published for the comparison of the b axes.…”
mentioning
confidence: 59%
See 2 more Smart Citations
“…Figure 4. Electrical resistivity for Al-PhBr.The Al 3+ ion of tris(oxalato)aluminate is smaller than previous examples, where M = Fe[13,17], Ga[28], Rh[30], and Ru[29] (T c =~3.8,~3.0,~2.9,~2.8 K, respectively, for G = bromobenzene), and the T c is smaller for M = Al at~2.5 K. A comparison of the b axis length of these bromobenzene salts at room temperature showed that the M = Fe salt has the longest at 20.0546(15) Å and also the highest~3.8 K [13,17]; M = Rh has an intermediate b axis of 20.0458(4) Å and a T c of~2.9 K [30]; while M = Al has the shortest b axis of 19.9472(4) Å and the lowest T c at~2.5 K. A direct comparison with the M = Ga[28] and Ru[29] salts cannot be made owing to A = K x (H 3 O) 1-x rather than H 3 O for these salts. Salts with M = Cr[23] and Mn[17] have been reported with T c s of 1.5 K and 2.0 K, respectively, but crystal structures are not published for the comparison of the b axes.…”
mentioning
confidence: 59%
“…Higher Tc salts in the Day series have higher Hc2 values (2-5 T) [52], and these quasi-2D superconductors are strongly anisotropic [53]. The Al 3+ ion of tris(oxalato)aluminate is smaller than previous examples, where M = Fe [13,17], Ga [28], Rh [30], and Ru [29] (Tc = ~3.8, ~3.0, ~2.9, ~2.8 K, respectively, for G = bromobenzene), and the Tc is smaller for M = Al at ~2. [28] and Ru [29] salts cannot be made owing to A = Kx(H3O)1-x rather than H3O for these salts.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…A final interesting aspect of this series is the presence of a structural transition from the high-temperature monoclinic C2/c space group to a triclinic P-1 one below ca. 200 K, only observed in the salts with G = PhF (19,20), PhCl (17,18), PhBr (15, 16), 2-Clpy (29, 30) and 2-Brpy (31,32). The first preliminary observation of this transition was reported in compound (ET) 4 [(H 3 O)Fe(C 2 O 4 ) 3 ]•PhBr (15,16), where a change in the unit cell parameters to a lower symmetry phase was observed at ca.…”
Section: β"-Bedt-ttf Salts With the [Fe(c 2 O 4 ) 3 ] 3− Anionmentioning
confidence: 99%
“…Over the past three decades, tris(oxalato)metalate(III) complex anions, [M(C 2 O 4 ) 3 ] 3-, have been extensively used for the design of many compounds with fascinating physical properties (Zhong et al, 1990;Bé nard et al, 2001;Coronado et al, 2008;Pardo et al, 2011;Martin et al, 2017;Tsobnang et al, 2019;O " kawa et al, 2020). One of the main reasons for that is the ability of these anions to act like ligands towards a variety of metallic cations and to build a diversity of extended structures in which neighboring metallic ions are linked through bridging oxalate ligands.…”
Section: Chemical Contextmentioning
confidence: 99%